ANALISIS PENGARUH PROFITABILITAS, UKURAN PERUSAHAAN, LEVERAGE, DAN KEPEMILIKAN INSTITUSIONAL TAX AVOIDANCE - Jesselin Vemberain; Yustina Triyani (Jurnal Akuntansi, 2021)
Tax avoidance is a scheme that aims to minimize the tax burden by taking advantage of loopholes in the tax provisions of a country. Tax avoidance is a practice carried out by individual and corporate taxpayers to reduce the tax burden that must be paid without violating the applicable tax laws. This study aims to analyze the effect of profitability, firm size, leverage and institutional ownership on tax avoidance. This study uses the basic theory : agency theory and compliance theory. The object of the research is a manufacturing company in the consumer goods industry sector which is listed on the Indonesia Stock Exchange during the 2016-2019 period. Researchers conducted descriptive statistical tests, coefficient similarity test (pooling), classical assumption test, multiple linear analysis, and hypothesis testing. The conclusion is that there is sufficient evidence that profitability and firm size have a negative effect on tax avoidance, while there is insufficient evidence that leverage has a positive effect on tax avoidance, and there is not sufficient evidence that institutional ownership has a negative effect on tax avoidance. Key word : profitability, firm size, leverage, institutional ownership,  tax avoidance References: Arianandini, P. W., & Ramantha, I. W. (2018). Pengaruh Profitabilitas, Leverage, dan Kepemilikan Institusional Pada Tax Avoidance. E-Jurnal Akuntansi, 22, 2088–2116. https://doi.org/10.24843/eja.2018.v22.i03.p17 Darmayanti, P. P. B., & Merkusiwati, N. K. L. A. (2019). Pengaruh Ukuran Perusahaan, Profitabilitas, Koneksi Politik dan Pengungkapan Corporate Social Responsibility Pada Tax Avoidance. E-Jurnal Akuntansi, 26, 1992–2019. https://doi.org/10.24843/eja.2019.v26.i03.p12 Dewanti, I. G. A. D. C., & Sujana, I. K. (2019). Pengaruh Ukuran Perusahaan, Corporate Social Responsibility, Profitabilitas dan Leverage pada Tax Avoidance. E-Jurnal Akuntansi, 28, 377. https://doi.org/10.24843/eja.2019.v28.i01.p15 Dewi, N. L. P. P., & Noviari, N. (2017). Pengaruh Ukuran Perusahaan, Leverage, Profitabilitas dan Corporate Social Responsibility Terhadap Penghindaran Pajak (Tax Avoidance). E-Jurnal Akuntansi, 21(2), 830–859. https://doi.org/10.24843/EJA.2017.v21.i02.p01 Dewinta, I. A. R., & Setiawan, P. E. (2016). Pengaruh Ukuran Perusahaan, Umur Perusahaan, Profitabilitas, Leverage, Dan Pertumbuhan Penjualan Terhadap Tax Avoidance. E-Jurnal Akuntansi Universitas Udayana, 14(3), 1584–1613. Ekonomi Bung Hatta. (2020). Ukuran Perusahaan (Pengertian, Jenis, Kriteria dan Indikator). https://ekonomi.bunghatta.ac.id/index.php/id/artikel/811-ukuran-perusahaan-pengertian-jenis-kriteria-dan-indikator diakses tanggal 12 Januari 2021 Fiandri, K. A., & Muid, D. (2017). Pengaruh Kepemilikan Institusional Dan Ukuran Perusahaan Terhadap Tax Avoidance Dengan Kinerja Keuangan Sebagai Variabel Mediasi Padaperusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesiatahun 2011 – 2014. Diponegoro Journal of Accounting, 6(2), 31–43. Fitria, G. N. (2018). Pengaruh Kepemilikan Institusional, Komisaris Independen, Karakter Eksekutif Dan Size Terhadap Tax Avoidance. Jurnal Profita : Komunikasi Ilmiah Akuntansi Dan Perpajakan, 11(3), 94–104. http://publikasi.mercubuana.ac.id/index.php/profita/article/view/4315 Gitman, L. J., & Zutter, C. J. (2012). Principles of Managerial Finance, Thirteenth Edition. England : Pearson Education Limited. Hidayat, W. W. (2018). Pengaruh Profitabilitas, Leverage Dan Pertumbuhan Penjualan Terhadap Penghindaran Pajak. Jurnal Riset Manajemen Dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 3(1), 19–26. https://doi.org/10.36226/jrmb.v3i1.82 Jensen, M. C., & Meckling, W. H. (1976). Theory of the firm: Managerial Behavior, Agency Costs and Ownership Structure. Journal of Financial Economics, 3(4), 305–360. https://doi.org/https://doi.org/10.1016/0304-405X(76)90026-X Kushariadi, B., & Putra, R. N. (2018). Good Corporate Governance, Leverage, Ukuran Perusahaan Dan Tax Avoidance. Journal of Islamic Finance and Accounting, 1(2), 1-18. https://doi.org/10.22515/jifa.v1i2.1401 Oktamawati, M. (2017). Pengaruh Karakter Eksekutif, Komite Audit, Ukuran Perusahaan, Leverage, Pertumbuhan Penjualan, Dan Profitabilitas Terhadap Tax Avoidance. Jurnal Akuntansi Bisnis, 15(1), 23–40. https://doi.org/10.24167/JAB.V15I1.1349 Pitaloka, S., & Merkusiwati, N. K. L. A. (2019). Pengaruh Profitabilitas, Leverage, Komite Audit, dan Karakter Eksekutif Terhadap Tax Avoidance. E-Jurnal Akuntansi, 27, 1202-1230. https://doi.org/10.24843/eja.2019.v27.i02.p14 Prasetyo, I., & Pramuka, B. A. (2018). Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, dan Proporsi Dewan Komisaris Independen terhadap Manajemen Laba. Jurnal Ekonomi, Bisnis, Dan Akuntansi (JEBA), 20(2), 1–15. https://doi.org/10.32616/jbr.v1i2.64 Putra, I. G. L. N. D. C., & Merkusiwati, N. K. L. A. (2016). Pengaruh Komisaris Independen, Leverage, Size dan Capital Intensity Ratio pada Tax Avoidance (Studi pada Perusahaan Manufaktur di Bursa Efek Indonesia Periode 2012-2014). E-Jurnal Akuntansi Universitas Udayana, 17(1), 690–714. https://ojs.unud.ac.id/index.php/Akuntansi/article/view/22025 Putri, A. A., & Lawita, N. F. (2019). Pengaruh Kepemilikan Institusional Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan. Jurnal Akuntansi & Ekonomika, 9(1), 68–75. https://doi.org/10.32795/widyaakuntansi.v1i1.249 Putri, V. R., & Putra, B. I. (2017). Pengaruh Leverage, Profitability, Ukuran Perusahaan Dan Proporsi Kepemilikan Institusional Terhadap Tax Avoidance. Jurnal Manajemen Dayasaing, 19(1), 1-11. https://doi.org/10.23917/dayasaing.v19i1.5100 Rahayu, S. K. (2017). Perpajakan (Konsep dan Aspek Formal). Bandung : Rekaya Sains. Riyanto, B. (2013). Dasar-Dasar Pembelanjaan Perusahaan. BPFE. Sintyawati, N. L. A., & Dewi, M. R. (2018). Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional Dan Leverage Terhadap Biaya Keagenan Pada Perusahaan Manufaktur. E-Jurnal Manajemen Universitas Udayana, 7(2), 993-1020. https://doi.org/10.24843/EJMUNUD.2018.v7.i02.p16. Tahar, A., & Rachman, A. K. (2014). Pengaruh Faktor Internal dan Faktor Eksternal Terhadap Kepatuhan Wajib Pajak. Jurnal Akuntansi Dan Investasi, 15(1), 56–67. Tebiono, J. N., & Sukanda, I. B. N. (2019). Faktor-Faktor yang mempengaruhi Tax Avoidance pada Perusahaan Manufaktur yang terdaftar Di BEI. Jurnal Bisnis Dan Akuntansi, 21(1), 121–130. http://jurnaltsm.id/index.php/JBA Utari, N. K. Y. U., & Supadmi, N. L. (2017). Pengaruh Corporate Governance, Profitabilitas Dan Koneksi Politik Pada Tax Avoidance. E-Jurnal Akuntansi Universitas Udayana, 18(3), 2202–2230. Yudea. (2018). Pengaruh Mekanisme Corporate Governance, Ukuran Perusahan, dan Leverage Terhadap Tax Avoidance. Jurnal Reviu Akuntansi Dan Keuangan, 21(2), 115–124. Zain, M. (2005). Manajemen Perpajakan. Jakarta : Salemba Empat.